Enhanced SDIoT Security Framework Models - Seongho Choi; Jin Kwak (International Journal of Distributed Sensor Networks)
Following the recent increase in the interest in IoT (Internet of Things) environment, devices that provide various services are being developed. As the diversity, research is required for efficient management of these devices and enhanced security. Previous network environments tend to be dependent on network devices and have difficulties in active processing of variable traffic. Moreover, it is expected that new or variant attacks will increase as packets of various patterns are generated from numerous devices, and hence immense research effort is required in solving this problem. In order to address such problems, this study aims to investigate strategies for establishing a security framework for the configuration of a software-defined IoT environment and efficient provision of security services. Moreover, the service to reduce the overhead involved in security service provision is configured, and a simple test is conducted to verify the feasibility of the proposed model.